Illocutionary Speech Acts in Oprah Winfrey’s Motivational Speech: A Pragmatic Study - Warsidi Warsidi; Siti Nurul Syakila; Dahniar Dahniar (Journal of English Language Teaching and Linguistics, 2023)
Pragmatic studies have been widely conducted, but speech acts on motivational speeches were rarely investigated. Moreover, functions of illocutionary speech acts are received very limited scholarly attention. These gaps have been encouraging the researchers to conduct the present to analyze speech acts contained in Oprah Winfrey’s motivational speeches with two purposes. First, it is to identify the forms of illocutionary speech acts in Oprah's motivational speech. Second, it also determines the function of illocutionary speech acts in Oprah's motivational speech. It employed a qualitative and quantitative method for the analysis. Then, in collecting data, it used note-taking as an instrument. In this regard, we watched and listened to five motivational videos of Oprah Winfrey’s speeches four times, and then took notes of any utterances containing forms and functions of illocutionary speech acts. Then, for analyzing data, we classified the forms of speech acts using a theory from Searle (1969) and functions of speech acts employing an analytical framework from Leech (1993). The results show various forms and functions in delivering a motivational speech. However, most speech acts in the videos tend to be assertive rather than the others, and concerning functions, they tend to be collaborative. The reason behind these dominances is discussed in this paper.